Biomarkers in the era of targeted therapy in giant cell arteritis and polymyalgia rheumatica: is it possible to replace acute-phase reactants? - Carvajal Alegria, Guillermo; Nicolas, Mathilde; van Sleen, Yannick (Frontiers in Immunology, 2023)
Research into giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) has become more important in the last few decades. Physicians are facing several challenges in managing the diagnosis, treatment, and relapses of GCA and PMR patients. The search for biomarkers could provide elements to guide a physician’s decision. In this review, we aim to summarize the scientific publications about biomarkers in GCA and PMR in the past decade. The first point raised by this review is the number of clinical situations in which biomarkers could be useful: differential diagnosis of either GCA or PMR, diagnosis of underlying vasculitis in PMR, prediction of relapse or complications, disease activity monitoring, choice, and modification of treatments. The second point raised by this review is the large number of biomarkers studied, from common markers like C-reactive protein, erythrocyte sedimentation rate, or elements of blood count to inflammatory cytokines, growth factors, or immune cell subpopulations. Finally, this review underlines the heterogeneity between the studies and proposes points to consider in studies evaluating biomarkers in general and particularly in the case of GCA and PMR.